Information Acquisition by Price-Setters and Monetary Policy - Volker Hahn (ETH Zurich, CER-ETH - Center of Economic Research, 2007)
In this paper we examine a model where firms decide on the intensity of information acquisition about shocks. We analyze how the monetary policy framework impacts on the aggregate amount of information collected by firms. We show that it is socially beneficial to delegate monetary policy to a conservative central bank even if there are no incentives to push output above its long-run level. Transparency of central banks about economic shocks has ambiguous e ects on welfare. If an extreme level of opacity is feasible, it represents the social optimum. Otherwise full transparency may be a second-best solution.
Keywords: E58; E13; E12; 330; conservative central banker; optimal monetary policy; information; acquisition; Phillips curve; transparency; Informationsversorgung; Preisführer; Unvollkommener Wettbewerb; Geldpolitik; Schock; Politische Kommunikation; Phillips-Kurve; Theorie